Linear accelerator-based stereotactic radiosurgery in 140 brain metastases from malignant melanoma - Hauswald, Henrik; Stenke, Alina; Debus, Juergen; Combs, Stephanie E. (BMC Cancer, 2015)
Background: To retrospectively access outcome and prognostic parameters of linear accelerator-based stereotactic radiosurgery in brain metastases from malignant melanoma. Methods: Between 1990 and 2011 140 brain metastases in 84 patients with malignant melanoma (median age 56 years) were treated with stereotactic radiosurgery. At initial stereotactic radiosurgery 48 % of patients showed extracerebral control. The median count of brain metastases in a single patient was 1, the median diameter was 12 mm. The median dose applied was 20 Gy/80 % isodose enclosing. Results: The median follow-up was 7 months and the median overall survival 9 months. The 6-, 12- and 24 month overall survival rates were 71 %, 39 % and 25 % respectively. Cerebral follow-up imaging showed complete remission in 20 brain metastases, partial remission in 39 brain metastases, stable disease in 54 brain metastases, progressive disease in 24 brain metastases and pseudo-progression in 3 brain metastases. Median intracerebral control was 5.3 months and the 6- and 12-month intracerebral progression-free survival rates 48 % and 38 %, respectively. Upon univariate analysis, extracerebral control (log-rank, p < 0.001), the response to stereotactic radiosurgery (log-rank, p < 0.001), the number of brain metastases (log-rank, p = 0.007), the recursive partitioning analysis class (log-rank, p = 0.027) and the diagnosis-specific graded prognostic assessment score (log-rank, p = 0.011) were prognostic for overall survival. The most common clinical side effect was headache common toxicity criteria grade I. The most common radiological finding during follow-up was localized edema within the stereotactic radiosurgery high dose region. Conclusion: Stereotactic radiosurgery is a well-tolerated and effective treatment option for brain metastases in malignant melanoma and was able to achieve local remissions in several cases. Furthermore, especially patients with controlled extracerebral disease and a low count of brain metastases seem to benefit from this treatment modality. Prospective trials analysing the effects of combined stereotactic radiosurgery and new systemic agents are warranted.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Brain metastases; Malignant melanoma; Radiotherapy; SRS; Stereotactic radiosurgery